GAS CHROMATOGRAPHY-MASS SPECTROSCOPY ANALYSIS OF BIOACTIVE COMPOUNDS EXTRACTED FROM THE PLANT GLYCOSMIS PENTAPHYLLA RETZ. USING VARIOUS SOLVENTS - VYSHNAVY DEVY DK; RUBY S; KUMAR M; SAJITH KUMAR PN; VIJAYAKUMAR B (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The main motive behind this work is to study the individual phyto compounds present in Glycosmis pentaphylla Retz. commonly known as Orange berry through gas chromatography-mass spectroscopy (GC-MS) analysis. The plant contains secondary metabolites such as alkaloids, flavonoids, glycosides, terpenoids, phenolic compounds, and coumarins. However, there was a lack of proper information regarding the chemistry of these phytocompounds specifically. Methods: The above objective was achieved through GC-MS method, both the ethanolic and hexane extract were prepared by maceration method. Then subjected to GC-MS analysis where the extract passed through fused silica column. Using the chromatogram the score, reverse match score and probability percentage were matched based on NIST and WILLEY library databases. Results: The compounds in the ethanolic extract being Octadecyl 2-pentanyl sulfite, 4-amino-1-(4-fluorophenyl)pentan-1-one, Neophytadiene, 3,7,11,15-Tetramethyl-2-hexadecen-1-ol, Ethyl hexadecanoate, Phytol, 11-Dodecyn-1-ol acetate, Acetyleugenol, and in the hexane extract were 1- nitro- 2-propanol, Butyraldehyde semicarbazone, 4- hydrazino-5-hydroxyimino-4,5,6,7-tetrahydrobenzofuran, 3-cyclohexene-1-ethanol, 9-cyclohptadecen- 1-one, N-methyl-2-nitropyridin-3-amine, 3-methyl-1,3-pentadiene, 4,7,8-trimethoxy-2,3-dihydrofuro[2,3-b]quinoline, 9,12-octadecadienoyl chloride, dihydromyrcene, and octadeca-9,12-dien-1-ol. These were noted along with their structure, molecular weight, chemical nature, etc., and displayed in the table. Furthermore, the theoretical action of the compounds was studied. Herewith, the presence of many potential compounds in the plant-G. pentaphylla was revealed. Conclusion: From the observations, it is obvious that ethanolic extract has more compounds than the hexane extract of the plant G. pentaphylla Retz. having medicinal value. It supports the activity-based studies in near future. After thorough analysis, these plant derived medicaments were found to have promising therapeutic potential as reported in various databases. Hence it can lead to the discovery of newer phytocompounds.